THE ROLE OF ROHIS MENTORS IN ENHANCING 21ST-CENTURY SKILLS OF STUDENTS AT MAN 1 SEMARANG - Muhammad Desvito Adrian; Saida Nur Sakila; Safiratul Khasanah; Muh. Hadidz (Yayasan Amanah Nur Aman, 2026)
Strengthening 21st-century skills is a crucial priority for educational institutions, particularly Islamic schools, to enable students to respond to global challenges critically, creatively, collaboratively, and communicatively. However, current religious development programs have not fully incorporated the enhancement of these competencies, especially within Islamic Spiritual Organizations (Rohis). This study aims to explore how Rohis instructors at MAN 1 Semarang support students in developing 21st-century skills and to identify the strategic approaches implemented through informal religious activities. Employing a descriptive qualitative method, the research involved Rohis instructors and student members as participants. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings reveal that Rohis instructors serve multiple roles, including organizational managers, mentors, educators, role models, facilitators, and motivators. Through routine meetings, religious community service programs, public speaking training, and the production of digital dakwah media, instructors successfully integrated 4C competencies. As a result, students’ religious values, critical thinking, communication skills, teamwork, and creativity improved significantly. Nonetheless, several challenges were identified, such as limited instructor capacity, the absence of standardized assessment tools, and time constraints.